Equivalent Fall Risk in Elderly Patients on Hemodialysis and Peritoneal Dialysis. Issue 1 (January 2016) - Farragher, Janine; Rajan, Tasleem; Chiu, Ernest; Ulutas, Ozkan; Tomlinson, George; Cook, Wendy L.; Jassal, Sarbjit V.
♦ Background: Accidental falls are common in the hemodialysis (HD) population. The high fall rate has been attributed to a combination of aging, kidney disease-related morbidity, and HD treatment-related hazards. We hypothesized that patients maintained on peritoneal dialysis (PD) would have fewer falls than those on chronic HD. The objective of this study was to compare the falls risk between cohorts of elderly patients maintained on HD and PD, using prospective data from a large academic dialysis facility. ♦ Methods: Patients aged 65 years or over on chronic in-hospital HD and PD at the University Health Network were recruited. Patients were followed biweekly, and falls occurring within the first year recorded. Fall risk between the 2 groups was compared using both crude and adjusted Poisson lognormal random effects modeling. ♦Results: Out of 258 potential patients, 236 were recruited, assessed at baseline, and followed biweekly for falls. Of 74 PD patients, 40 (54%) experienced 86 falls while 76 out of 162 (47%) HD patients experienced a total of 305 falls (crude fall rate 1.25 vs 1.60 respectively, odds ratio [OR] falls in PD patients 0.78, 95% confidence interval [CI] 0.61 – 0.92, p = 0.04). After adjustment for differences in comorbidity, number of medications, and other demographic differences, PD patients were no less likely to experience accidental falls than HD patients (OR 1.63, 95% CI 0.88 – 3.04, p = 0.1). ♦ Conclusions: We conclude that accidental falls are equally common in the PD population and the HD population. These data argue against post-HD hypotension as the sole contributor to the high fall risk in the dialysis population.